ANALISIS KEBUTUHAN AIR TANAMAN DENGAN METODE CAOLI PADA TANAMAN TOMAT DENGAN IRIGASI TETES DI LAHAN KERING LOMBOK UTARA - I DEWA GEDE JAYA NEGARA; M. BAGUS BUDIANTO; ANID SUPRIYADI; HUMAIRO SAIDAH (Universitas Mahasaraswati Mataram, 2020)
Tomato farming in the dry land of Salut Village, North Lombok is very often done by farmers, because the plants are short-lived and the selling price of the harvest is quite stable. However, the development of tomato plants in this region is still constrained by the high demand for plant water (KAT), because there are not many references. For this reason, this study aims to determine the amount of water needed for tomato planting and other parameters for each growth phase (f). The study is conducted on a land measuring 7m x 28 m, the size of the beds around 0.75 m x 28 m, the source of water from a tank with a capacity of 1600m3 and drip irrigation for crop irrigation. KBT analysis used a formula (Caoli, 1967), with analysis data from field data when planting tomatoes, so the results of the study are expected to be more realistic to address these obstacles in the development of tomato plants in the district of North Lombok. KAT analysis results with the Caolli formula show, for once irrigation in the initial phase (f1) around 0.738 m3, the active vegetative phase (f2) around 1.667 m3 and the fertilization phase until maturation of the initial fruit (f3) around 3.087 m3. The amount of soil moisture (w) additional irrigation in each phase is for f1 around 4% -5%, f2 around 6.5% -12% and f3 around 12% -17%. The duration of drip irrigation by 40 minutes needs to be shortened in phase f1, for phase f2 the duration is sufficient, and in phase f3 the duration needs to be added by more than 40 minutes or the irrigation schedule is shortened to less than 4.